KUALITAS NUTRISI AMPAS KELAPA (Cocos nucifera L.) FERMENTASI MENGGUNAKAN Aspergillus niger - Heri Kurniawan (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This research was aimed to observe the effect of usage of Aspergillus niger for fermenting coconut dregs (Cocos Nucifera L.) on its nutrition quality. Aspergillus niger obtained from Biochemical and Nutrition Laboratory of Animal Science Faculty on UGM, Yogyakarta was optimalized at coconut oil and coconut dregs as substrat. Variable was perceived for example enzyme lipase production, the quality of physical (pH, texture, color, aroma), and chemical composition of coconut dregs, steamed coconut dregs, fermented coconut dregs and steamed fermented coconut dregs. The result showed that Aspergillus niger producted highest enzyme of lipase in four days incubation either at coconut oil (0.85U/ml) and coconut dregs (1.81U/ml) as substrat. The treatment of steaming and fermenting of coconut dregs affected of pH, tekstur, color, aroma as will as decreased dry materials (12.75 and 16.24%), crude fat (13.11 and 29.20%), organic materials (5.21 and 16.89%) but increased crude protein (11.84%), crude fibre (24.85 and 36.81%) and extract materials without nitrogen (10.28 and 23.97%). It could be concluded that Aspergillus niger have activity of lipase which high enough so that can degraded fat content of coconut dregs. (Key word: Aspergillus niger, Coconut dregs, Fermentation)